2016
DOI: 10.1007/s00455-015-9681-7
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Incidence of Patient-Reported Dysphagia After Anterior Cervical Decompression and Fusion with the Zero-Profile Implant System

Abstract: Dysphagia is a well-known complication following anterior cervical surgery. It has been reported that the Zero-profile Implant System can decrease the incidence of dysphagia following surgery, however, dysphagia after anterior cervical decompression and fusion (ACDF) with the Zero-profile Implant System remains controversial. Previous studies only focus on small sample sizes. The objective of this study was to determine the incidence of dysphagia after ACDF with the Zero-profile Implant System. Studies were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 43 publications
1
12
1
Order By: Relevance
“…The anterior approach is commonly used to treat numerous cervical spine pathologies, such as degenerative, traumatic, inflammatory and congenital diseases. Dysphagia following anterior cervical spine surgery (ACSS) is one of the most common complications, with the reported incidence from 1.7 to 88% [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The anterior approach is commonly used to treat numerous cervical spine pathologies, such as degenerative, traumatic, inflammatory and congenital diseases. Dysphagia following anterior cervical spine surgery (ACSS) is one of the most common complications, with the reported incidence from 1.7 to 88% [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the following factors to be associated with higher possibility of dysphagia after anterior cervical surgery: female patients, older patients, C4-5 surgery, anterior plating, long operation time, multi-level surgery, and use of bone morphogenetic protein. [2729] Theoretically anterior C2-3 surgery was expected to result in a higher incidence of postoperative dysphagia due to the special location and difficult exposure which often requires a much more powerful traction strength during surgery. The Hangman fracture patients often suffered from edema of the esophagus and prevertebral soft tissue which can contribute to the occurrence of dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…Its prevalence following anterior cervical spine surgery ranges from 2% to 60% depending on disease severity and the time frame of assessment. [36] Surgical level, multilevel surgery, female patients, and instrumentation are related to an increased prevalence of postoperative dysphagia, but CDR could significantly reduce postoperative dysphagia compared with ACDF. [37,38] In our meta-analysis, we also found that dysphagia had lower occurrences rate in the CDR group than the ACDF group.…”
Section: Discussionmentioning
confidence: 99%